A Review of Demographic, Medical, and Treatment Variables Associated with Health-Related Quality of Life (HRQOL) in Survivors of Hematopoietic Stem Cell (HSCT) and Bone Marrow Transplantation (BMT) during Childhood - Reinfjell, Trude; Tremolada, Marta; Zeltzer, Lonnie K. (Frontiers in Psychology, 2017)
Hematopoietic stem cell transplantation (HSCT) is a standard treatment after disease relapse and failure of conventional treatments for cancer in childhood. HSCT is associated with adverse side effects, prolonged hospitalization, and isolation. Previous studies have shown that survivors of HSCT are at particularly high risk for developing late effects and medical complications. Quality-of-life issues after treatment has therefore become an important focus. This review of health-related quality of life (HRQOL) in long-term cancer survivors of HSCT in childhood investigated: 1) the long-term impact of HSCT in childhood cancer survivors on HRQOL; 2) the fixed (i.e., socio-demographic and illness factors) and modifiable (cognitive and psychological functioning, resources) variables predicting HRQOL outcome in HSCT childhood cancer survivors; 3) the methodology (instruments, type of studies, timing of assessment, type of transplantation) adopted to screen HRQOL issues. A search of 3 databases identified a total of 9 studies published between January 2006 and August 2016, including 2 prospective cohort studies measuring HRQOL and 7 cross-sectional studies. All studies reported a follow-up time of 5 years or longer. The results showed that HRQOL is significantly impacted in the longer term after HSCT in childhood, and risk factors such as the presence of a severe chronic health condition or a major medical condition, graft vs host disease (GVHD) and pain are present. Continual evaluation of HRQOL must be integrated into follow-up after HSCT in childhood cancer, and intervention for those survivors with poor HRQOL should be offered. Longitudinal studies should be emphasized in future research.